2021
DOI: 10.4103/genint.genint_3_21
|View full text |Cite
|
Sign up to set email alerts
|

Association of Telomere Length and Serum Vitamin D Levels with Type 2 Diabetes Mellitus and its Related Complications: A Possible Future Perspective

Abstract: Evidence show that shortened telomere length (TL) and low Vitamin D levels can increase the risk of type 2 diabetes mellitus (T2DM) and its associated complications. T2DM has been considered as an age-related disease, it may be associated with TL. The study aimed to evaluate the association of TL and Vitamin D levels with complications of T2DM and the impact of Vitamin D on TL in patients with T2DM. This 1-year cross-sectional study was conducted at a tertiary care hospital on 90 patients. Height, weight, body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Similarly, two independent studies on elderly subjects also reported that serum 25-Hydroxyvitamin D is positively associated with mean telomere length suggesting that levels of 25-Hydroxyvitamin D could be predictors of telomere length and longevity (Beilfuss et al, 2017 ; Richards et al, 2007 ). Another recent study suggests that higher levels of vitamin D are positively related to longer telomere length but negatively associated with indications of type II diabetes as monitored through levels of Hb1Ac suggesting a deeper correlation between vitamin D, and cellular senescence, and age-related diseases (Akash et al, 2021 ). In addition to vitamin D, vitamin E is also reported to have anti-cellular senescence attributes which could be attributed to its strong antioxidant activity.…”
Section: Primary Diet Constituents and Cellular Senescencementioning
confidence: 99%
“…Similarly, two independent studies on elderly subjects also reported that serum 25-Hydroxyvitamin D is positively associated with mean telomere length suggesting that levels of 25-Hydroxyvitamin D could be predictors of telomere length and longevity (Beilfuss et al, 2017 ; Richards et al, 2007 ). Another recent study suggests that higher levels of vitamin D are positively related to longer telomere length but negatively associated with indications of type II diabetes as monitored through levels of Hb1Ac suggesting a deeper correlation between vitamin D, and cellular senescence, and age-related diseases (Akash et al, 2021 ). In addition to vitamin D, vitamin E is also reported to have anti-cellular senescence attributes which could be attributed to its strong antioxidant activity.…”
Section: Primary Diet Constituents and Cellular Senescencementioning
confidence: 99%